EVALUASI PENGALAMAN BELAJAR MAHASISWA DALAM PEMBELAJARAN JARAK JAUH: STUDI KASUS DI UMN - Riatun, Riatun; Alvin, Silvanus (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Distance Learning (PJJ) took centre stage in the world of education when the Covid-19 pandemic hit. The times and social dynamics that occur demand a rapid adaptation process. Therefore, in the scope of higher education, PJJ is a necessity. Multimedia Nusantara University (UMN) is one of the universities that presents a PJJ programme in the field of Communication Science. This research aims to find out the experience of Communication Science PJJ students in using e-Learning. This research is important to know the students' behaviour pattern so that it is useful for decision making to provide optimal education for students. This research is descriptive quantitative. A total of 67 students became respondents. There are three main findings: Firstly, the majority of students access e-Learning using laptop devices; Secondly, the majority of students access e-Learning using internet connection from home; Thirdly, PJJ discussion forums are less attractive to students